[LETTER RE: FIRE SAFE CIGARETTE ACT] - MCGARY,RA (Tufts Archival Research Center, 2007)
Missing Attachments; Letter from Roger McGary to Donald Mooney about Fire Safe Cigarette Act. Indicates support of act by Joint Council of National Fire Service Organizations.